2022
DOI: 10.1177/10781552221074281
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multifocal Leukoencephalopathy Among Ibrutinib Treatment In Chronic Lymphocytic Leukemia

Abstract: Introduction: Both chronic lymphocytic leukemia (CLL) itself and the drugs used for its treatment, pose a risk for progressive multifocal leukoencephalopathy (PML). Although the relationship between Rituximab and PML is well known, case reports that have been recently published, suggest that ibrutinib; which is used in the treatment of CLL, may increase the risk of PML. Case report: Here, we report a case of 64 year-old female patient with CLL who was previously treated with rituximab, fludarabine and bendamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In fact, PML-IRIS lesion neuroimaging demonstrates contrast enhancement, mass effect, and interstitial edema [32]. But even in cases of hematological malignancies, these findings may differ across possible other prior medical conditions and the drugs that may be used to treat them [38][39][40].…”
Section: Neuropathobiology Of Pmlmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PML-IRIS lesion neuroimaging demonstrates contrast enhancement, mass effect, and interstitial edema [32]. But even in cases of hematological malignancies, these findings may differ across possible other prior medical conditions and the drugs that may be used to treat them [38][39][40].…”
Section: Neuropathobiology Of Pmlmentioning
confidence: 99%
“…Concerning CSF, apart from the viral DNA, in HIV-infected PML patients, pleocytosis was not common but increased protein levels could be possible in almost half of the patients, yet abnormal decreases in glycose level may not be observed [88]. For the IRIS-PML cases, a study reported that the total leukocyte count median was 1 cell/mm 3 (0-2), while the median glucose and protein levels were 61 mg/dL (50-69) and 36 mg/dL (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), respectively [89]. A study on CSF analysis in 108 patients with PML demonstrated that compared to the routine CSF parameters, 22% had an elevated cell count and 35% showed an increased Qalbumin indicating a disturbed blood-CSF-barrier; the mean lactate content was 1.64 mmol/L, whereby 6% presented with elevated lactate levels; PML patients showed an increased cell count-mainly driven by HIV-PML cases, among whom a significantly higher proportion had a disturbed blood-CSF-barrier function [99].…”
Section: Imaging Features Of Pmlmentioning
confidence: 99%
“…A fertőző betegségek körébe tartozik a súlyos, sokszor halálos neurológiai tünetekkel járó progresszív multifokális leukoenkefalopátia, melyet a John Cunningham vírus reaktivációja okoz. Előfordulása extrém ritka, melyről pontos statisztikai adatok nem állnak rendelkezésre, esetleírások anti-CD20-kezelések nélkül, modern terápiák mellett is előfordulnak [44]. A CLL11 tanulmányban a citopéniák előfordulása nagyobb volt obinutuzumab mellett, de ez nem társult egyéb súlyos mellékhatások fokozott gyakoriságával [43].…”
Section: Anti-cd20-kezelésunclassified